Rényi’s Entropy, Statistical Order and van der Waals Gas - Pennini, Flavia Catalina (2022)
The notion of statistical order derives from the disequilibrium concept introduced by López-Ruiz, Mancini, and Calbet thirty years ago. In this effort, it is shown that the disequilibrium is intimately linked to the celebrated Rényi entropy. One also explores this link in connection with the van der Waals gas description.